Survei Minat Belajar Siswa dalam Mengikuti Pendidikan Jasmani, Olahraga dan Kesehatan - Winarno; Demon, Fransiskus Dominikus; Wahyudi, Edi; Afandi, Achmad; Mushofi, Yuskhil; Sudarsono (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The purpose of the study was to determine students' interest in participating in PJOK learning at SMPT CLC Tunas Perwira in the 2023/2024 academic year. Tunas Perwiara School is a special school for children of Indonesian workers in Malaysia. The method used in this study is a quasi-experimental design that allows to test the effect of student interest on sports learning outcomes. The learning achievement test analysis was conducted using the pared sample t test. The sample used 22 students. Based on the analysis, description, testing, and discussion, it can be concluded that there is an effect of student interest in participating in sports learning. This can be seen from the tcount value of 5.779 which is greater than the ttable which is 1.795, with a sig value of 0.001 which is smaller than 0.05. In addition, the presentation results show a figure of 73.09% which indicates a positive influence of learning interest on student achievement in sports learning at Tunas Perwira School Tawau Sabah Malaysia.